POST-INDEPENDENCE HIGHER EDUCATION SYSTEM: INITIAL REFORMS (1991-2000) (Scientific journal of the Fergana State University, 2026)
Since the early years of independence, the Republic of Uzbekistan has identified the fundamental reform of all sectors, particularly the higher education system, as one of its key strategic priorities. This is because one of the main drivers of modern global development is human capital that possesses high qualifications, advanced knowledge, and practical skills. Ensuring the competitiveness of the higher education system, integrating it into the global educational space, and training specialists in accordance with the dynamic demands of the labor market have today become integral components of national development. This article analyzes the political-legal, organizational, and pedagogical reforms carried out in Uzbekistan’s higher education system between 1991 and 2000, the processes of integration into international standards, and the mechanisms, effectiveness, and outcomes of measures aimed at improving the quality of higher education.